Training as an Effort to Improve Knowledge, Attitude and Skills as a Motivator of Exclusive Breastfeeding - Sri Wahyuni; Ni Wayan Dian Ekayanthi; Yulina Eva Riany; Zahro Malihah; Aisyah Aisyah (JURNAL KEBIDANAN, 2024)
The absolute estimate for non-exclusive breastfed babies in West Java Province is 384,270 babies. The success of exclusive breastfeeding cannot be separated from the support of the people around him. This support needs to be built with training for the community to promote the importance of exclusive breastfeeding. The research design is a mixed method, namely qualitative and quantitative. Qualitative research with in-depth interviews and quasi-experimental quantitative research with a one group pre-test post test design by providing a form of intervention, namely training. The population is entirely female in Bogor City. Samples were taken in qualitative research using a snowball technique until the results were saturated, quantitative research consisted of two groups: Ordinary and Extraordinary  mothers in the City of Bogor. The research sample was 5 people using qualitative methods and 35 people using quantitative methods. The qualitative method statistical test uses content analysis, the quantitative method uses Wilcoxon test analysis. As a result of in-depth interviews, it was found that the materials needed to make a pocket book as an educational training medium were breastfeeding techniques, communication techniques and knowledge about exclusive breastfeeding. The results of quantitative research show that there is a significant relationship between training with a p value of less than 0.05 on knowledge in the elderly group, attitudes in the cadre group, and meaningful motivation skills in all groups, namely cadre groups, community leaders, elderly people, ordinary women. Training/education using pocket books is able to increase abilities as a motivator for exclusive breastfeeding in the city of Bogor. There is a need to follow up on the use of pocket books and encourage mothers who have been trained to become exclusive breastfeeding motivators to be able to motivate pregnant women to successfully breastfeed exclusively.